Heterochromatin heterogeneity in Hypostomus prope unae (Steindachner, 1878) (Siluriformes, Loricariidae)from Northeastern Brazil - Bitencourt, J.A. (Pensoft Publishers, 2011)
Abstract. Cytogenetic analyses using C-banding and chromosomal digestion by several restriction enzymes were carried out in four populations (named A, B, C and D) of Hypostomus prope unae (Loricariidae, Hypostominae) from Contas river basin, northeastern Brazil. These populations share 2n=76 and single NORs on the second metacentric pair but exclusive karyotype forms for each locality. Populations A and B presented conspicuous terminal and interstitial heterochromatic blocks on most of acrocentric chromosomes and equivalent to NORs with differences in both position and bearing pair. Population D showed evident marks at interstitial regions and interspersed with nucleolar region while population C presented interstitial and terminal heterochromatin segments, non-coincident with NORs. The banding pattern after digestion with the endonucleases Alu I, Bam HI, Hae III and Dde I revealed a remarkable heterogeneity within heterochromatin, allowing the identification of distinctive clusters of repeated DNA in the studied populations, besides specific patterns along euchromatic regions. The analysis using restriction enzymes has proved to be highly informative, characterizing population differences and peculiarities in the genome organization of Hypostomus prope unae.